Vacuum cup capable of improving heat insulation performance and preparation method of vacuum cup
By using composite hollow glass microbead components and expanded perlite aerogel insulation materials in the thermos cup, the problem of insufficient insulation performance of the existing thermos cup is solved, and a more efficient insulation effect is achieved.
Patent Information
- Application Number
- CN202411903651.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The thermal insulation performance of existing thermos cups is difficult to meet the ever-increasing insulation needs.
Using composite hollow glass microbead components and expanded perlite aerogel insulation material, an efficient thermal insulation coating is formed by combining hollow glass microbeads with modified graphene and using the combination of expanded perlite and silica aerogel.
The thermal conductivity coefficient is significantly reduced, the overall insulation performance of the thermos cup is improved, and the insulation performance of the thermos cup is significantly improved.
Abstract
Description
Technical Field
[0001] The present application relates to the field of thermos cups, and in particular to a thermos cup with improved thermal insulation performance and a preparation method thereof. Background Art
[0002] A thermos cup is generally a water container made of ceramic or stainless steel with a vacuum layer. It has a lid on the top and is tightly sealed. The vacuum insulation layer can delay the heat dissipation of the water or other liquids inside to achieve the purpose of heat preservation.
[0003] Thermos cups evolved from thermos bottles. The heat preservation principle is the same as that of thermos bottles, but people made the bottle into a cup for convenience. There are three ways for heat to spread: radiation, convection and transfer. The silver cup liner in the thermos cup can reflect the radiation of hot water, and the vacuum between the cup liner and the cup body can block the transfer of heat.
[0004] As people's living standards improve, the demand for insulation of thermos bottles is also increasing. Therefore, the requirements for the thermal insulation performance of thermos bottles are also increasing. The current insulation performance of thermos bottles can no longer meet the demand. Summary of the invention
[0005] In order to further improve the thermal insulation performance of a thermos cup, the present application provides a thermos cup with improved thermal insulation performance and a preparation method thereof.
[0006] The present application provides a thermos cup with improved thermal insulation performance and a preparation method thereof, which adopts the following technical solutions: In the first aspect, the present application provides a thermos cup with improved thermal insulation performance, which adopts the following technical solution: A thermos cup with improved thermal insulation performance, comprising a thermos cup liner, a thermal insulation coating and a thermos cup shell, wherein the thermal insulation coating is obtained by coating a thermal insulation coating on the surface of the thermos cup liner, and the thermal insulation coating comprises the following components in parts by weight: 48-56 parts of waterborne polyurethane, 26-32 parts of waterborne acrylic acid, 12-16 parts of composite hollow glass microsphere component, and 8-10 parts of expanded perlite aerogel insulation material; The composite hollow glass microsphere components include hollow glass microspheres and modified graphene.
[0007] By adopting the above technical scheme, the outer wall of the inner liner of the thermos cup is coated with thermal insulation coating to form a thermal insulation coating. The composite hollow glass microsphere component is prepared by hollow glass microspheres and modified graphene in the thermal insulation coating. The hollow glass microspheres have a hollow structural characteristic and form a vacuum state, which can effectively reduce the heat conduction of gas molecules, thereby greatly reducing the thermal conductivity and further improving the overall thermal insulation performance of the system. By combining with modified graphene, the thermal conductivity of the hollow glass microspheres can be further reduced, thereby synergistically improving the thermal insulation performance of the thermos cup.
[0008] Preferably, the composite hollow glass microsphere component is prepared by the following method: The hollow glass microbeads are added into a hydrochloric acid solution, magnetically stirred, washed, and dried to obtain acidified glass microbeads; the modified graphene is added into an aqueous solution of sodium dodecylbenzenesulfonate, ultrasonically obtained into a modified graphene suspension, the acidified glass microbeads are added into the modified graphene suspension, magnetically stirred to obtain a composite suspension, the composite suspension is filtered, and dried to obtain a composite hollow glass microbead component.
[0009] By adopting the above technical solution, the modified graphene is coated on the surface of the hollow glass microspheres, and the bonding tightness between the components in the hollow glass microspheres is improved, thereby further improving the vacuum insulation performance of the hollow glass microspheres and reducing heat loss, thereby further improving the thermal insulation performance of the composite hollow glass microspheres and improving the thermal insulation performance of the thermos cup.
[0010] Preferably, the modified graphene oxide is prepared by the following method: After mixing graphene, water and ethanol, ultrasonic dispersion is performed to obtain a graphene dispersion liquid; after mixing KH570, water and ethanol, stirring is performed to obtain a silane coupling agent solution; after mixing the graphene dispersion liquid and the silane coupling agent solution, the temperature is increased to react, and then washed, filtered and freeze-dried to obtain modified graphene.
[0011] By adopting the above technical scheme, after KH-570 is grafted onto the graphene surface, the number of active groups on the graphene surface is increased, and the dispersion performance of graphene in the system is improved. At the same time, the modified graphene has good binding performance. After the modified graphene is combined with the hollow glass microspheres, the prepared composite hollow glass microsphere components can be connected more tightly, and the composite hollow glass microsphere components are arranged more tightly in the system, so as to improve the thermal insulation performance of the vacuum insulation, thereby further improving the thermal insulation performance of the prepared thermos cup.
[0012] Preferably, the mass ratio between the acid-washed hollow glass microspheres and the modified graphene oxide is 1:(0.12-0.16).
[0013] By adopting the above technical solution, the mass ratio between the acid-washed hollow glass microspheres and the modified graphene oxide is preferably within the above range, so that the prepared composite hollow glass microsphere components can be more stable.
[0014] Preferably, the expanded perlite aerogel thermal insulation material comprises expanded perlite and silica aerogel.
[0015] By adopting the above technical solution, expanded perlite is a natural acidic volcanic lava with pores inside. It is an inorganic thermal insulation material with good performance. When added to the thermos material system, it can synergistically improve the thermal insulation performance with the hollow glass microsphere component. Silica aerogel has good thermal insulation performance, specific surface area and porosity, and can also improve the thermal insulation performance of the thermos. After combining the expanded perlite with the silica aerogel, the overall thermal insulation performance of the system can be further improved, thereby improving the thermal insulation performance of the thermos.
[0016] Preferably, the expanded perlite aerogel thermal insulation material is prepared by the following method: Tethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol and water are mixed to obtain a mixed solution, which is magnetically stirred in a water bath environment to obtain a hydrosol, which is added to a vacuum cylinder filled with expanded perlite, and the hydrogel is adsorbed into the pores of the expanded perlite by vacuum adsorption, and gelation is waited for. After the gelation is completed, a gel composite is obtained, which is placed in anhydrous ethanol for treatment, and the treated gel composite is mixed with trimethylchlorosilane, ethanol and n-hexane for treatment. After the treatment, the expanded perlite aerogel thermal insulation material is obtained by washing and drying.
[0017] By adopting the above technical scheme, the hydrosol is adsorbed into the voids of the expanded perlite by vacuum adsorption, and then the expanded perlite aerogel thermal insulation material is prepared through aging treatment and drying. At the same time, the surface of the gel composite is hydrophobically treated with trimethylchlorosilane, so that the hydrophilic -OH group is replaced by the hydrophobic -CH3, so as to further reduce the water penetration and affect the thermal insulation performance of the thermos cup thermal insulation material, and the stability of the thermos cup is further improved.
[0018] Preferably, the particle size of the expanded perlite is 2.0-3.5 mm.
[0019] By adopting the above technical solution, preferably the particle size of the expanded perlite is within the above range, the adsorption rate of the aerogel can be further improved, thereby improving the performance of the prepared expanded perlite aerogel.
[0020] Preferably, during the vacuum pump adsorption treatment, the vacuum adsorption time is 22-24 minutes.
[0021] By adopting the above technical solution, it is preferred that the vacuum adsorption time is within the above range, so that the adsorption amount of the aerogel is further improved, thereby improving the stability of the prepared expanded perlite aerogel.
[0022] In a second aspect, the present application provides a method for preparing a thermos cup with improved thermal insulation performance, using the following technical solution: A method for preparing a thermos cup with improved thermal insulation performance comprises the following steps: A thermal insulation coating is obtained by mixing water-based acrylic acid, water-based polyurethane, composite hollow glass microsphere components, and expanded perlite aerogel thermal insulation materials. The thermal insulation coating is applied to the outer surface of the inner liner of a thermos cup and dried to form a layer of thermal insulation coating on the outer surface of the inner liner of the thermos cup. The inner liner of the thermos cup and the outer shell of the thermos cup are installed to obtain a thermos cup with improved thermal insulation performance.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. The hollow glass microsphere component is prepared by combining hollow glass microspheres with modified graphene. The hollow glass microspheres have the characteristics of a hollow structure, forming a vacuum state, which can effectively reduce the heat conduction of gas molecules, thereby greatly reducing the thermal conductivity coefficient. After the modified graphene is combined with the hollow glass microspheres, the modified graphene is coated on the surface of the hollow glass microspheres, and the modified graphene and the hollow glass microspheres are tightly combined. At the same time, the compatibility and tightness of the hollow glass microspheres in the system can be improved, which can further reduce heat conduction, thereby synergistically improving the thermal insulation performance of the prepared thermos cup; 2. Using expanded perlite as a carrier, the silica aerogel is embedded into the cavities of the expanded perlite through vacuum adsorption, thereby obtaining an expanded perlite aerogel thermal insulation material, which improves the bonding performance between the silica aerogel and the expanded perlite, effectively improves the mechanical properties and stability of the thermal insulation material, and synergistically improves the overall thermal insulation performance of the system, thereby further improving the thermal insulation performance of the thermos cup. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples are commercially available; the inner liner of the thermos cup is made of stainless steel 304, and the outer shell of the thermos cup is made of plastic.
[0025] Example 1 Preparation of modified graphene: 5 g of graphene, 50 g of deionized water and 400 g of ethanol were mixed, and then ultrasonically dispersed to obtain a graphene dispersion; 5 g of KH570 (CAS No.: 2530-85-0), 50 g of deionized water and 400 g of ethanol were mixed, and the pH of the system was adjusted to 4 with 2 mol / L hydrochloric acid, and then stirred for 2 h to obtain a silane coupling agent solution, and the graphene dispersion was mixed with the silane coupling agent solution, and then the temperature was raised to 60° C. to react for 6 h, and then washed with ethanol, filtered, and freeze-dried at -20° C. to obtain modified graphene.
[0026] Preparation of composite hollow glass microsphere components: The hollow glass microspheres were added to a 1M hydrochloric acid solution, magnetically stirred for 12 hours, then washed with deionized water until the pH value of the eluent was above 5, and dried in a vacuum oven at 100°C for 18 hours to obtain acidified glass microspheres; 2.14 g of modified graphene was added to a 1% mass concentration of sodium dodecylbenzene sulfonate (CAS No.: 25155-30-0) aqueous solution, ultrasonicated at a frequency of 25 kHz for 60 minutes to obtain a modified graphene suspension, 17.86 g of acidified glass microspheres were added to the modified graphene suspension, magnetically stirred at a speed of 600 r / min for 6 hours to obtain a composite suspension, and finally the composite suspension was filtered through a 0.22 μm nylon membrane, and dried in an oven at 100°C for 12 hours to obtain a composite hollow glass microsphere component.
[0027] Preparation of expanded perlite aerogel insulation material: 20 g of tetraethyl orthosilicate (CAS No.: 78-10-4), 20 g of methyltriethoxysilane (CAS No.: 2031-67-6), 120 g of anhydrous ethanol and 40 g of deionized water were mixed to obtain a mixed solution, and the pH of the mixed solution was adjusted to 2.5 using a hydrochloric acid solution. The mixed solution was magnetically stirred for 30 min in a water bath at 25° C., and then ammonia water was added to adjust the pH to 7. The gelation time was controlled at 60 min to obtain a hydrosol. The hydrosol was added to a vacuum cylinder containing 20 g of expanded perlite with a particle size of 2-3.5 mm, and then the hydrogel was adsorbed into the pores of the expanded perlite by a circulating water vacuum pump. During vacuum adsorption, the vacuum degree was 0. 04MPa, the vacuum adsorption time is 22min; after vacuum adsorption, the vacuum pump is turned off and gelation is waited. After gelation is completed, a gel composite is obtained, and the gel composite is placed in anhydrous ethanol, and the temperature is controlled at 120°C for aging treatment. The gel composite after aging treatment is added to a mixed solution of 20g of trimethylchlorosilane (CAS No.: 75-77-4), 30g of ethanol and 5g of n-hexane (CAS No.: 110-54-3) for treatment. After treatment, the system is washed with n-hexane, and then in a drying oven, the temperature is increased from 25°C to 140°C at a heating rate of 10°C / h, and then cooled to 25°C to obtain an expanded perlite aerogel thermal insulation material.
[0028] Prepare the thermos cup: 48g of aqueous acrylic acid, 26g of aqueous polyurethane, 12g of composite hollow glass microsphere component, and 8g of expanded perlite aerogel insulation material are mixed to obtain a thermal insulation coating, which is applied to the outer surface of the inner liner of a thermos cup. After drying for 12 hours, a layer of thermal insulation coating is formed on the outer surface of the inner liner of the thermos cup. The inner liner of the thermos cup and the outer shell of the thermos cup are installed to obtain a thermos cup with improved thermal insulation performance.
[0029] Example 2 Preparation of modified graphene: 5 g of graphene, 50 g of deionized water and 400 g of ethanol were mixed, and then ultrasonically dispersed to obtain a graphene dispersion; 5 g of KH570, 50 g of deionized water and 400 g of ethanol were mixed, and the pH of the system was adjusted to 4 with 2 mol / L hydrochloric acid, and then stirred for 2 h to obtain a silane coupling agent solution. After the graphene dispersion and the silane coupling agent solution were mixed, the temperature was raised to 60° C. to react for 6 h, and then washed with ethanol, filtered, and freeze-dried at -20° C. to obtain modified graphene.
[0030] Preparation of composite hollow glass microsphere components: The hollow glass microspheres were added to a 1M hydrochloric acid solution, magnetically stirred for 12 hours, then washed with deionized water until the pH value of the eluent was above 5, and dried in a vacuum oven at 100°C for 18 hours to obtain acidified glass microspheres; 2.76 g of modified graphene was added to a sodium dodecylbenzene sulfonate aqueous solution with a mass concentration of 1%, ultrasonicated at a frequency of 25 kHz for 60 minutes to obtain a modified graphene suspension, 17.24 g of acidified glass microspheres were added to the modified graphene suspension, magnetically stirred at a speed of 600 r / min for 6 hours to obtain a composite suspension, and finally the composite suspension was filtered through a 0.22 μm nylon membrane, and dried in an oven at 100°C for 12 hours to obtain a composite hollow glass microsphere component.
[0031] Preparation of expanded perlite aerogel insulation material: 20 g of tetraethyl orthosilicate, 20 g of methyltriethoxysilane, 120 g of anhydrous ethanol and 40 g of deionized water were mixed to obtain a mixed solution, and the pH of the mixed solution was adjusted to 2.5 using a hydrochloric acid solution. The mixture was magnetically stirred for 30 min in a water bath at 25° C., and then ammonia water was added to adjust the pH to 7. The gelation time was controlled at 60 min to obtain a hydrosol. The hydrosol was added to a vacuum cylinder containing 20 g of expanded perlite with a particle size of 2-3.5 mm, and then the hydrogel was adsorbed into the pores of the expanded perlite by a circulating water vacuum pump. During vacuum adsorption, the vacuum degree was 0. 04MPa, the vacuum adsorption time is 24min; after vacuum adsorption, the vacuum pump is turned off and gelation is waited. After gelation is completed, a gel composite is obtained, the gel composite is put into anhydrous ethanol, the temperature is controlled at 120°C, and an aging treatment is performed. The gel composite after aging treatment is added to a mixed solution of 20g of trimethylchlorosilane, 30g of ethanol and 5g of n-hexane for treatment. After treatment, the system is washed with n-hexane, and then the temperature is increased from 25°C to 140°C in a drying oven at a heating rate of 10°C / h, and then cooled to 25°C to obtain an expanded perlite aerogel thermal insulation material.
[0032] Prepare the thermos cup: 56g of aqueous acrylic acid, 32g of aqueous polyurethane, 16g of composite hollow glass microsphere component, and 10g of expanded perlite aerogel insulation material are mixed to obtain a thermal insulation coating, which is applied to the outer surface of the inner liner of a thermos cup. After drying for 12 hours, a layer of thermal insulation coating is formed on the outer surface of the inner liner of the thermos cup. The inner liner of the thermos cup and the outer shell of the thermos cup are installed to obtain a thermos cup with improved thermal insulation performance.
[0033] Example 3 Preparation of modified graphene: 5 g of graphene, 50 g of deionized water and 400 g of ethanol were mixed, and then ultrasonically dispersed to obtain a graphene dispersion; 5 g of KH570, 50 g of deionized water and 400 g of ethanol were mixed, and the pH of the system was adjusted to 4 with 2 mol / L hydrochloric acid, and then stirred for 2 h to obtain a silane coupling agent solution. After the graphene dispersion and the silane coupling agent solution were mixed, the temperature was raised to 60° C. to react for 6 h, and then washed with ethanol, filtered, and freeze-dried at -20° C. to obtain modified graphene.
[0034] Preparation of composite hollow glass microsphere components: The hollow glass microspheres were added to a 1M hydrochloric acid solution, magnetically stirred for 12 hours, then washed with deionized water until the pH value of the eluate was above 5, and dried in a vacuum oven at 100°C for 18 hours to obtain acidified glass microspheres; 2.46 g of modified graphene was added to a sodium dodecylbenzene sulfonate aqueous solution with a mass concentration of 1%, ultrasonicated at a frequency of 25 kHz for 60 minutes to obtain a modified graphene suspension, 17.54 g of acidified glass microspheres were added to the modified graphene suspension, magnetically stirred at a speed of 600 r / min for 6 hours to obtain a composite suspension, and finally the composite suspension was filtered through a 0.22 μm nylon membrane, and dried in an oven at 100°C for 12 hours to obtain a composite hollow glass microsphere component.
[0035] Preparation of expanded perlite aerogel insulation material: 20 g of tetraethyl orthosilicate, 20 g of methyltriethoxysilane, 120 g of anhydrous ethanol and 40 g of deionized water were mixed to obtain a mixed solution, and the pH of the mixed solution was adjusted to 2.5 using a hydrochloric acid solution. The mixture was magnetically stirred for 30 min in a water bath at 25° C., and then ammonia water was added to adjust the pH to 7. The gelation time was controlled at 60 min to obtain a hydrosol. The hydrosol was added to a vacuum cylinder containing 20 g of expanded perlite with a particle size of 2-3.5 mm, and then the hydrogel was adsorbed into the pores of the expanded perlite by a circulating water vacuum pump. During vacuum adsorption, the vacuum degree was 0. 04MPa, the vacuum adsorption time is 23min; after vacuum adsorption, the vacuum pump is turned off and gelation is waited. After gelation is completed, a gel composite is obtained, and the gel composite is placed in anhydrous ethanol, the temperature is controlled at 120°C, and an aging treatment is performed. The gel composite after aging treatment is added to a mixed solution of 20g of trimethylchlorosilane, 30g of ethanol and 5g of n-hexane for treatment. After treatment, the system is washed with n-hexane, and then the temperature is increased from 25°C to 140°C in a drying oven at a heating rate of 10°C / h, and then cooled to 25°C to obtain an expanded perlite aerogel thermal insulation material.
[0036] Prepare the thermos cup: 52g of aqueous acrylic acid, 29g of aqueous polyurethane, 14g of composite hollow glass microsphere component, and 9g of expanded perlite aerogel insulation material are mixed to obtain a thermal insulation coating, which is applied to the outer surface of the inner liner of a thermos cup. After drying for 12 hours, a layer of thermal insulation coating is formed on the outer surface of the inner liner of the thermos cup. The inner liner of the thermos cup and the outer shell of the thermos cup are installed to obtain a thermos cup with improved thermal insulation performance.
[0037] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the composite hollow glass microsphere component, the amount of modified graphene used is 1.65g, and the amount of hollow glass microspheres used is 18.35g.
[0038] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the composite hollow glass microsphere component, the amount of modified graphene used is 3.79g, and the amount of hollow glass microspheres used is 16.81g.
[0039] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the composite hollow glass microsphere component, the modified graphene is replaced by ordinary graphene.
[0040] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that when preparing the expanded perlite aerogel thermal insulation material, the particle size of the expanded perlite selected is 0.9-2 mm.
[0041] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the expanded perlite aerogel thermal insulation material, the particle size of the expanded perlite selected is 3.5-4 mm.
[0042] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the expanded perlite aerogel thermal insulation material, the vacuum adsorption time is 19 minutes.
[0043] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the expanded perlite aerogel thermal insulation material, the vacuum adsorption time is 26 minutes.
[0044] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the expanded perlite aerogel insulation material, vacuum adsorption is not performed, and the aged silica aerogel is only mixed with the expanded perlite to obtain the aerogel.
[0045] Comparative Example 1 Comparative Example 1 is based on Example 3, and in Comparative Example 1, the composite hollow glass microsphere component is replaced with an equal amount of ordinary hollow glass microspheres.
[0046] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the expanded perlite aerogel insulation material is replaced with an equal amount of ordinary expanded perlite.
[0047] Comparative Example 3 Comparative Example 3 is based on Example 3, and in Comparative Example 3, the expanded perlite aerogel insulation material is replaced with an equal amount of silica aerogel.
[0048] Performance testing The following performance tests were performed on the samples of Examples 1-11 and Comparative Examples 1-2: Thermal insulation performance test The thermal conductivity of the sample was tested and the test results were filled in Table 1.
[0049] Table 1 Performance test results of Examples 1-11 and Comparative Examples 1-2 Test items Thermal conductivity (W / m·K) Example 1 0.042 Example 2 0.040 Example 3 0.037 Example 4 0.068 Example 5 0.071 Example 6 0.087 Example 7 0.134 Example 8 0.094 Example 9 0.064 Example 10 0.041 Embodiment 11 0.143 Comparative Example 1 0.196 Comparative Example 2 0.187 As can be seen from Table 1, the thermal conductivities of Examples 1-3 are all 0.045 W / m·K or less, indicating that the thermos cup prepared in the present application has good thermal insulation performance.
[0050] In Examples 4 and 5, when preparing the composite hollow glass microsphere components, the mass ratio of the modified graphene to the hollow glass microspheres is not within the range specified in the present application. When the content of the modified graphene is too little, the coverage of the surface of the hollow glass microspheres decreases, making it difficult to further improve the compatibility of the prepared hollow glass microspheres, and the stability in the system decreases, affecting the vacuum thermal insulation performance of the hollow glass microspheres; when the content of the modified graphene is too much, the excessive modified graphene is difficult to evenly coat the surface of the hollow glass microspheres, so that the particle size of the hollow glass microspheres is different, the uniformity of the hollow glass microspheres in the system decreases, affecting the stability of the thermal insulation coating, so the thermal insulation performance of Examples 4 and 5 is reduced.
[0051] In Example 6, the modified graphene is replaced with ordinary graphene. The unmodified graphene has poor binding performance with the hollow glass microspheres, making it difficult to uniformly coat the hollow glass microspheres, which affects the dispersion performance of the hollow glass microspheres in the system. At the same time, ordinary graphene agglomerates in the system, further affecting the stability of the system. Therefore, the thermal insulation performance of Example 6 decreases.
[0052] In Example 7 and Example 8, when preparing the expanded perlite aerogel thermal insulation material, the particle size of the expanded perlite is not within the range specified in the present application. When the particle size of the expanded perlite is too small, the void network structure inside the small expanded perlite is small, and it is difficult to adsorb more silica aerogel and fill the voids, so the thermal insulation effect is difficult to improve; when the particle size of the expanded perlite is too large, the binding ability of the expanded perlite is difficult to be further improved, and the dispersion effect in the system is reduced, which will also affect the thermal insulation performance of the expanded perlite aerogel thermal insulation material. Therefore, the thermal insulation performance of Example 7 and Example 8 is reduced, and Example 9 When preparing the expanded perlite aerogel thermal insulation material in Example 10, the vacuum adsorption time is not within the range specified in the present application. When the vacuum adsorption time is too short, it is difficult for the voids in the expanded perlite to adsorb a sufficient amount of silica aerogel to fill the expanded perlite, thereby reducing the loading capacity of the expanded perlite on silica, affecting the thermal insulation performance of the expanded perlite aerogel; when the vacuum adsorption time is too long, as the internal voids are filled with aerogel, the voids that can be filled by the expanded perlite become fewer and fewer, the resistance becomes greater and greater, and it is difficult to further load more silica aerogel, so it is difficult to further improve the thermal insulation effect.
[0053] Example 11 was prepared by mixing only the aged silica aerogel and the expanded perlite. The bonding performance between the unloaded expanded perlite and the silica aerogel was difficult to be further modified, which affected the thermal insulation performance. Therefore, the thermal insulation performance of Example 11 was reduced.
[0054] In Comparative Example 1, the composite hollow glass microspheres are replaced with ordinary hollow glass microspheres. The compatibility of ordinary hollow glass microspheres is difficult to be further improved, and the binding performance in the system is difficult to be improved, which affects the overall thermal insulation performance of the system.
[0055] No silica aerogel was added in Comparative Example 1, and no expanded perlite was added in Comparative Example 2. The thermal insulation performance of a single component was difficult to be further improved, resulting in gaps between the coatings. Therefore, the thermal insulation performance of Comparative Examples 1 and 2 was reduced.
[0056] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A thermos cup with improved thermal insulation performance, characterized in that: It includes a thermos cup liner, a thermal insulation coating and a thermos cup shell. The thermal insulation coating is obtained by coating the thermal insulation coating on the surface of the thermos cup liner. The thermal insulation coating includes the following components in parts by weight: 48-56 parts of waterborne polyurethane, 26-32 parts of waterborne acrylic acid, 12-16 parts of composite hollow glass microsphere component, and 8-10 parts of expanded perlite aerogel insulation material; The composite hollow glass microsphere components include hollow glass microspheres and modified graphene.
2. A thermos cup with improved thermal insulation performance according to claim 1, characterized in that: The composite hollow glass microsphere component is prepared by the following method: The hollow glass microbeads are added into a hydrochloric acid solution, magnetically stirred, washed, and dried to obtain acidified glass microbeads; the modified graphene is added into an aqueous solution of sodium dodecylbenzenesulfonate, ultrasonically obtained into a modified graphene suspension, the acidified glass microbeads are added into the modified graphene suspension, magnetically stirred to obtain a composite suspension, the composite suspension is filtered, and dried to obtain a composite hollow glass microbead component.
3. A thermos cup with improved thermal insulation performance according to claim 2, characterized in that: The modified graphene oxide is prepared by the following method: After mixing graphene, water and ethanol, ultrasonic dispersion is performed to obtain a graphene dispersion liquid; after mixing KH570, water and ethanol, stirring is performed to obtain a silane coupling agent solution; after mixing the graphene dispersion liquid and the silane coupling agent solution, the temperature is increased to react, and then washed, filtered and freeze-dried to obtain modified graphene.
4. A thermos cup with improved thermal insulation performance according to claim 3, characterized in that: The mass ratio between the acid-washed hollow glass microspheres and the modified graphene oxide is 1:(0.12-0.16).
5. The thermos cup with improved thermal insulation performance according to claim 1, characterized in that: The expanded perlite aerogel thermal insulation material comprises expanded perlite and silicon dioxide aerogel.
6. The thermos cup with improved thermal insulation performance according to claim 5, characterized in that: The expanded perlite aerogel thermal insulation material is prepared by the following method: Tethyl orthosilicate, methyltriethoxysilane, anhydrous ethanol and water are mixed to obtain a mixed solution, which is magnetically stirred in a water bath environment to obtain a hydrosol, which is added to a vacuum cylinder filled with expanded perlite, and the hydrogel is adsorbed into the pores of the expanded perlite by vacuum adsorption, and gelation is waited for. After the gelation is completed, a gel composite is obtained, and the gel composite is placed in anhydrous ethanol for treatment, and the treated gel composite is mixed with trimethylchlorosilane, ethanol and n-hexane for treatment. After the treatment, the expanded perlite aerogel thermal insulation material is obtained by washing and drying.
7. A thermos cup with improved thermal insulation performance according to claim 6, characterized in that: The particle size of the expanded perlite is 2.0-3.5 mm.
8. The thermos cup with improved thermal insulation performance according to claim 6, characterized in that: During the vacuum pump adsorption treatment, the vacuum adsorption time is 22-24 minutes.
9. A method for preparing a thermos cup with improved thermal insulation performance as claimed in any one of claims 1 to 8, characterized in that: The steps include: A thermal insulation coating is obtained by mixing water-based acrylic acid, water-based polyurethane, composite hollow glass microsphere components, and expanded perlite aerogel thermal insulation materials. The thermal insulation coating is applied to the outer surface of the inner liner of a thermos cup and dried to form a layer of thermal insulation coating on the outer surface of the inner liner of the thermos cup. The inner liner of the thermos cup and the outer shell of the thermos cup are installed to obtain a thermos cup with improved thermal insulation performance.
Citation Information
Cited By
Inner container of electric water heater and preparation method
CN120363562A